2010
DOI: 10.1111/j.1742-7843.2009.00489.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Concentrative Nucleoside Transporter 1 Gene Polymorphism on Oral Bioavailability of Mizoribine in Stable Kidney Transplant Recipients

Abstract: Mizoribine, an immunosuppressive anti-metabolite, is largely excreted into urine in its unchanged form, and its pharmacokinetics has been considered to be dependent on the glomerular filtration rate. However, the pharmacokinetic disposition of mizoribine has not been fully clarified. The aim of this study was to evaluate the pharmacokinetic disposition of mizoribine based on polymorphism of concentrative nucleoside transporter (CNT) 1 gene in kidney transplant recipients. Thirty-four Japanese stable recipients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…Prior to our studies, the presence of the nucleo-pocket structure was unknown. Although our study with pyrrolo-gemcitabine serves merely as proof of concept, it is conceivable that the nucleo-pocket structure can be utilized in the design of nucleoside-derived drugs or prodrugs that can be specifically targeted only to cell types that express hCNT1 since expression levels of hCNT1 are closely related to the responsiveness of many different types of normal or cancer cells to chemotherapy treatment (Lane et al, 2010; Naito et al, 2010; Rabascio et al, 2010; Bhutia et al, 2011; Choi, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…Prior to our studies, the presence of the nucleo-pocket structure was unknown. Although our study with pyrrolo-gemcitabine serves merely as proof of concept, it is conceivable that the nucleo-pocket structure can be utilized in the design of nucleoside-derived drugs or prodrugs that can be specifically targeted only to cell types that express hCNT1 since expression levels of hCNT1 are closely related to the responsiveness of many different types of normal or cancer cells to chemotherapy treatment (Lane et al, 2010; Naito et al, 2010; Rabascio et al, 2010; Bhutia et al, 2011; Choi, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…We previously evaluated the membrane transport of mizoribine using human intestinal epithelial LS180 cells, and reported that the cellular uptake of mizoribine was mediated not only by CNT but also by ENT [7,8]. In addition, Naito et al [14] evaluated the effect of the genetic polymorphism of CNT1 565G[A on the bioavailability of mizoribine in Japanese kidney transplant recipients. The bioavailability of mizoribine in patients with CNT1-G/A and -A/A alleles was significantly lower than that with the CNT1-G/G allele.…”
Section: Discussionmentioning
confidence: 97%
“…The bioavailability of mizoribine in patients with CNT1-G/A and -A/A alleles was significantly lower than that with the CNT1-G/G allele. The authors therefore thought that CNT1 565G[A was one of the factors causing the variation in the bioavailability (intestinal absorption) of mizoribine [14]. However, the mechanisms responsible for interindividual variability in bioavailability of mizoribine have not yet been fully assessed.…”
Section: Discussionmentioning
confidence: 97%
“…Nevertheless, although particular polymorphisms may be relevant in terms of function, there still is a need for a better knowledge of their clinical relevance (Table 11.4). Combined genotype effect of CDA A-76C, dCK C-1205T, DCTD T-47C, hCNT3 1383 C<T, hENT1 T-549C and hENT1 C913T References: SLC28A1 (Gray et al, 2004a;Soo et al, 2009;Naito et al, 2010); SLC28A2 (Owen et al, 2005;Li et al, 2007Li et al, , 2009Soo et al, 2009;Yee et al, 2009); SLC28A3 (Badagnani et al, 2005;Errasti-Murugarren et al, 2008;Okazaki et al, 2010): SLC29A1 (Myers et al, 2006;Okazaki et al, 2010;Tanaka et al, 2010;Kim et al, 2011); SLC29A2 (Owen et al, 2006b); SLC29A3 (Molho-Pessach et al, 2008;Cliffe et al, 2009) …”
Section: Genetic Variability and Functional Consequencesmentioning
confidence: 99%
“…Presence of the hCNT1-Val189Ile is associated with increased thymidine uptake but also with a significantly lower affinity for the nucleoside analog gemcitabine (Gray et al, 2004a). This hCNT1 variant has also been linked to higher bioavailability of mizoribine in kidney transplant recipients (Naito et al, 2010) Another SLC28A1 variant, hCNT1-Asp521Asn, has been shown to be associated with the occurrence of neutropenia and thrombocytopenia in nonsmall cell lung cancer (NSCLC) patients receiving gemcitabine therapy, thus providing the first indication that the hCNT1 protein may be involved in the development of hematotoxicity and adverse drug reactions (ADRs) .…”
Section: Chapter 11 Nucleoside Transporters (Slc28 and Slc29) Familymentioning
confidence: 99%